2010
DOI: 10.1167/iovs.09-4188
|View full text |Cite
|
Sign up to set email alerts
|

Rose Bengal Staining of the Temporal Conjunctiva Differentiates Sjögren's Syndrome from Keratoconjunctivitis Sicca

Abstract: Rose bengal staining of the ocular surface is an important observation in the detection of SS and the differentiation of pSS and KCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Serum RF and ANA levels had strong linear correlations with conjunctival stain or the total OSS. In a 2010 study, Caffery et al 18 suggested that conjunctival staining is important for the diagnosis of both SS and non-SS dry eye. Rose Bengal stain (cornea and conjunctival stain) was significantly correlated with the plasma IgG level, suggesting B cell hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Serum RF and ANA levels had strong linear correlations with conjunctival stain or the total OSS. In a 2010 study, Caffery et al 18 suggested that conjunctival staining is important for the diagnosis of both SS and non-SS dry eye. Rose Bengal stain (cornea and conjunctival stain) was significantly correlated with the plasma IgG level, suggesting B cell hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of the subjects was 31.0 ± 6.4 years (range: [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] in Group 1,29.0 ± 4.41 years (range: [24][25][26][27][28][29][30][31][32][33][34][35][36][37] in Group 2. There were 9 female subjects and 1 male subject in Group 1; 18 female subjects and 2 male subjects in Group 2. Patients in Group 1 were diagnosed with primary SS according to the Revised European-American Classification System.…”
Section: Methodsmentioning
confidence: 99%
“…One of the characteristics of the conjunctival epithelium in SS patients with dry eye is that more severe dry-eye damage is observed compared with that of non-SS patients. 33 Various abnormalities, such as increased expression levels of inflammatory cytokines and their genes, decreased goblet cell density, and stratification and squamous metaplasia of the conjunctival epithelium have been reported in SS patients, 4,34-37 thus confirming that P2Y 2 receptor expression changes in the conjunctival epithelium of those patients. However, there was no correlation between ΔTMR and the conjunctival staining scores reflecting bulbar conjunctival epithelial damage.…”
Section: Discussionmentioning
confidence: 90%